Literasi keuangan dan pengelolaan keuangan keluarga dalam perspektif budaya Jawa dan Bugis - Reni Tri Purniawati; Lutfi Lutfi (Journal of Business & Banking, 2017)
Consumptive behavior can negatively affect family welfare. Financial literacy is one of the factors which may affect family financial management behavior. This family financial may differ across ethnic groups due to the different characters and principles of life among them. This study aimed to examine the effect of financial literacy on family financial management using ethnic as a moderating variable. This study uses a questionnaire instrument that is distributed to 140 respondents of Javanese in Madiun residency and 96 respondents of Bugis at Makassar, East Sulawesi. The data analysis technique is multiple regression analysis. This research use purposive sampling and convenience sampling as the sampling technique. The result of this study shows that financial literacy positively affect family financial management behavior, while ethnic does not moderate the effect of financial literacy on family financial management behavior. This study suggests that families, both Javanese and Bugis, need to enhance their financial literacy to enable them to manage their finance well so that they can improve their welfare.